2003
DOI: 10.1046/j.1600-0412.2003.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral misoprostol (100 μg) versus vaginal misoprostol (25 μg) in term labor induction: a randomized comparison

Abstract: Vaginal misoprostol in its currently recommended dose of 25 microg seems to be more efficacious than the 100 microg oral dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…There were no significant differences in the rates of vaginal delivery not achieved within 24 h, excessive uterine activity and cesarean section, neonatal or maternal outcomes. Higher instrumental vaginal delivery rates after oral misoprostol were reported in one study only (35.3% versus 14%; OR 3.35, 95% CI 1.25–8.96) [15]. In one study ( n = 153) misoprostol was used either 100 μg orally or 50 μg vaginally six hourly [13].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…There were no significant differences in the rates of vaginal delivery not achieved within 24 h, excessive uterine activity and cesarean section, neonatal or maternal outcomes. Higher instrumental vaginal delivery rates after oral misoprostol were reported in one study only (35.3% versus 14%; OR 3.35, 95% CI 1.25–8.96) [15]. In one study ( n = 153) misoprostol was used either 100 μg orally or 50 μg vaginally six hourly [13].…”
Section: Resultsmentioning
confidence: 89%
“…In two trials (n = 337) an oral misoprostol dose of 100 μg or vaginal dose of 25 μg every three or six hours was used [15,18]. There were no significant differences in the rates of vaginal delivery not achieved within 24 h, excessive uterine activity and cesarean section, neonatal or maternal outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing dinoprostone with misoprostol would allow considerable cost savings. Although misoprostol can be administered vaginally, orally or rectally, the vaginal route appears, at present, to offer the most benefits in terms of efficacy and minimising side effects 4–6 . Danielian et al 7 found that 50 μg of misoprostol was more effective than dinoprostone gel and had a similar side effect profile, but others have demonstrated that a dosing regimen of 50 μg or higher is associated with an increased incidence of uterine contraction abnormalities 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Early studies indicated that the risk of inducing fetal hypoxia occurs with fixed-dosage of misoprostol such as 100 μg orally or 25 μg vaginally every 4 hours (recommended dose) until adequate labor commences [8][9][10]. In one pilot study, small, frequent (every 2 hours), titrated doses of oral misoprostol minimized the risk of uterine hyperstimulation and prevented fetal hypoxia [11,12].…”
Section: Introductionmentioning
confidence: 99%